Process Support and Knowledge Representation in Health Care BPM 2012 Joint Workshop, ProHealth 2012/KR4HC 2012, Tallinn, Estonia, September 3, 2012, Revised Selected Papers - Lenz, Richard; Miksch, Silvia; Peleg, Mor; Reichert, Manfred; Riano, David; ten Teije, Annette (Lecture Notes in Artificial Intelligence, 2013)
This book constitutes thoroughly refereed revised selected papers from the BPM 2012 Joint Workshop on Process-Oriented Information Systems and Knowledge Representation in Health Care, ProHealth 2012/KR4HC 2012, held in Tallinn, Estonia, in September 2012. The 9 papers presented were carefully reviewed and selected from 19 submissions. In addition the book contains 1 keynote paper and 2 invited contributions. The papers are organized in topical sections named: guidelines and summarization; archetypes and cooperation; and process mining and temporal analysis.